Assessing e-health policy development process using policy process network approach - Mafani, Ncedisa (My University, 2013)
The use of information and communication technologies in health care system can enhance equitable access to health care services and health information, even for the most marginalised communities in South Africa. The effective implementation of such applications in the health care system is dependent on the inclusive e-health policy development process bringing together the views of all the different role players. This research paper is a qualitative case study which looks into the extent to which the e-health policy development process in the Republic of South Africa has involved the active participation of all the relevant role players. The policy process network (PPN) approach introduced by Parag (2005) has been utilised to guide the methodology employed, the selection of the participants in the study, the design of the research instrument and the analysis of the results. The research study has looked at the extent to which the assessment of the e-health development process is aligned to the policy process network (PPN) approach. This policy assessment has not followed all the elements employed in the PPN as the policy under investigation is still in its infancy stage. However, the PPN approach employed has assisted in detecting the weaknesses of the e-health policy and the e-health policy process. If applied correctly, the framework can contribute to the formulation of a policy that is more effective. In view of the research findings, it emerges that there is a centralised approach into e-health policy development process. The centralised approach has shown its own weaknesses as highlighted in the limited participation of local government, communities and the healthcare implementers. The recommendations are important for the National and Provincial Department of Health policy makers to note the complexity of e-health which requires a sophisticated and encompassing coordination and collaboration system of all the networks. Without such a system the role players would just wield their power instead of working together in the e-health policy development process.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: E-health; Medical policy; South Africa; Health care